Lactoferrin and lysozyme to promote nutritional, clinical and enteric recovery: a protocol for a factorial, blinded, placebo-controlled randomised trial among children with diarrhoea and malnutrition (the Boresha Afya trial) - Jie Liu; Grace John-Stewart; Barbra A Richardson; Indi Trehan; Ruchi Tiwari; Kirkby D Tickell; Mareme M Diakhate; Benson O Singa; Christine J McGrath; Patricia B Pavlinac; Doreen Rwigi; Judd L Walson; et al. (BMJ Open, 2024)
Introduction Children with moderate or severe wasting are at particularly high risk of recurrent or persistent diarrhoea, nutritional deterioration and death following a diarrhoeal episode. Lactoferrin and lysozyme are nutritional supplements that may reduce the risk of recurrent diarrhoeal episodes and accelerate nutritional recovery by treating or preventing underlying enteric infections and/or improving enteric function.Methods and analysis In this factorial, blinded, placebo-controlled randomised trial, we aim to determine the efficacy of lactoferrin and lysozyme supplementation in decreasing diarrhoea incidence and improving nutritional recovery in Kenyan children convalescing from comorbid diarrhoea and wasting. Six hundred children aged 6–24 months with mid-upper arm circumference <12.5 cm who are returning home after an outpatient visit or inpatient hospital stay for diarrhoea will be enrolled. Children will be randomised to 16 weeks of lactoferrin, lysozyme, a combination of the two, or placebo and followed for 24 weeks, with biweekly home visits by community health workers and clinic visits at 4, 10, 16 and 24 weeks. The primary analysis will compare the incidence of moderate-to-severe diarrhoea and time to nutritional recovery between each intervention arm and placebo. The trial will also test whether these interventions reduce enteric pathogen carriage, decrease enteric permeability and/or increase haemoglobin concentration in enrolled children. Finally, we will evaluate the acceptability, adherence and cost-effectiveness of lactoferrin and/or lysozyme.Ethics and dissemination The trial has been approved by the institutional review boards of the Kenya Medical Research Institute, the University of Washington, the Kenyan Pharmacy and Poisons Board, and the Kenyan National Commission on Science, Technology and Innovation. The results of this trial will be shared with local and international stakeholders and published in peer-reviewed journals, and the key findings will be presented at relevant conferences.Trial registration number NCT05519254, PACTR202108480098476.